Green in Software Engineering - Calero, Coral (Springer, 2015)
Sustainability is being demanded by our society today; we have become aware of the need to cut down on our energy consumption and reduce our carbon footprint. At an international level, there is a whole host of initiatives trying to tackle these issues, and the main research and development programmes include sizeable amounts of funding for projects seeking to achieve environmentally sound technologies...